Yield loss in East African highland banana (Musa spp., AAAEA group) caused by the banana weevil, Cosmopolites sordidus Germar - Rukazambuga, N.; Gold, C.; Gowen, S. (1998)
Yield loss in highland banana caused by the banana weevil, Cosmopolites sordidus, was studied in field trials in Uganda. Weevils were released at the base of banana mats 9 months after planting. Weevil populations, corm damage, plant growth and yield were assessed over four crop cycles. The effect of damage was greater on bunch weight than on plant growth and rate of development. Yield loss increased with crop cycle and ranged from 5% in the first cycle to 44% in the fourth cycle. The cumulative effect of heavy damage sustained over several crop cycles resulted in greater reduction in bunch weight than that inflicted by similar levels of damage in a single cycle. The data suggest that C. sordidus damage is a leading cause of highland banana decline and disappearance in central Uganda.